2021
DOI: 10.1021/acs.langmuir.1c02590
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsified Gel Formulations for Topical Delivery of Clotrimazole: Structural and In Vitro Evaluation

Abstract: Microemulsified gels (μEGs) with fascinating functions have become indispensable as topical drug delivery systems due to their structural flexibility, high stability, and facile manufacturing process. Topical administration is an attractive alternative to traditional methods because of advantages such as noninvasive administration, bypassing first-pass metabolism, and improving patient compliance. In this article, we report on the new formulations of microemulsion-based gels suitable for topical pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 82 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…Thereby, droplet size and viscosity are the main physical parameters with a direct impact on the drug release. A high level of the aqueous phase and the nanometer scale of the dispersed droplets sustain a faster diffusion, as previously described for microemulsions with clotrimazole [ 111 ]. Reduced droplet diameters between 119.60–188.33 nm, specific for the ME 1–ME 4 fluid systems, were correlated to higher values of diffusion coefficients, while in the case of ME 5–ME 8 gel-like systems, elevated sizes up to 250.20 nm slowed down the MCZ release.…”
Section: Resultsmentioning
confidence: 95%
“…Thereby, droplet size and viscosity are the main physical parameters with a direct impact on the drug release. A high level of the aqueous phase and the nanometer scale of the dispersed droplets sustain a faster diffusion, as previously described for microemulsions with clotrimazole [ 111 ]. Reduced droplet diameters between 119.60–188.33 nm, specific for the ME 1–ME 4 fluid systems, were correlated to higher values of diffusion coefficients, while in the case of ME 5–ME 8 gel-like systems, elevated sizes up to 250.20 nm slowed down the MCZ release.…”
Section: Resultsmentioning
confidence: 95%
“…Despite enhancing permeation, the natural oils used in this study are nontoxic and moisturizing, prevent the loss of electrolytes and fluids, and maintain skin tonicity. The inadequate drug solubility, dissolution, and permeation led to poor flux from the pure ketoconazole gel . Shahid and colleagues developed a ketoconazole-loaded cationic nanoemulsion for topical delivery against cutaneous fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…The inadequate drug solubility, dissolution, and permeation led to poor flux from the pure ketoconazole gel. 46 Shahid and colleagues developed a ketoconazole-loaded cationic nanoemulsion for topical delivery against cutaneous fungal infection. The authors reported a nanoemulsion size of 239 nm and the highest drug permeation of 95.34 ± 1.22 μg cm –2 .…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, dilutions of Smix with saline were prepared and titrated with IPM until the end. All the percentage values of the three components for each titration were plotted on a ternary phase diagram to demarcate the homogeneous (microemulsion) [ 3 ] region from the heterogeneous phase [ 30 , 31 ]. Three compositions were selected out of the homogeneous phase of the pseudo-ternary diagram, accounting for almost the same amount of oil, but different Smix and saline amounts.…”
Section: Methodsmentioning
confidence: 99%